Efektivitas Pembelajaran Matematika Materi Lingkaran di SMP Menggunakan Strategi Reciprocal Teaching - Nur, Fazriati; Anwar, Anwar; Fadhiliani, Dwi (Tirtamath: Jurnal Penelitian dan Pengajaran Matematika, 2025)
This study aims to determine the effectiveness of the application of reciprocal teaching strategy on circle in class VIII at SMP Negeri 8 Banda Aceh. This research is descriptive quantitative and uses pre-experimental design in the form of one-shot case study. The research sample was students of class VIII-5 SMP Negeri 8 Banda Aceh with a total of 29 students, who were taken by purposive sampling. The results of data analysis were obtained from student response questionnaires, student learning outcomes tests, student activity observations and observations of teacher ability to manage learning. The results of this study showed that (1) the teacher's ability to manage learning in the very good category with an average score of 3.79; (2) student activities during learning took place in a very active category reaching 97.42%; (3) student learning completeness was classically complete reaching a percentage of 86.20%; and (4) student responses in the very good category reached a percentage of 85.11%. Based on the research, it is concluded that the application of reciprocal teaching strategy is effective on circle material in class VIII at SMP Negeri 8 Banda Aceh. Therefore, future research needs to consider revealing students' thinking process in learning.